Spatiotemporal analysis of dune stabilization in the Kyzylkum and Karakum sandy deserts - Petrović, Marijana Z.; Blumberg, Dan G.; Orlovsky, Leah; Maman, Shimrit (Frontiers in Earth Science, 2023)
Sand seas and dune bedforms are climatic chronicles that have a wide range of scientific meanings. The Karakum and Kyzylkum sand seas in Central Asia span ∼500,000 km2, among the largest sand seas on Earth; yet, very little is known about their emergence and stabilization. Further, the internationally accessible literature lacks comprehensive studies on the interactions between contemporary climate and dune morphodynamics for this region. In this study, we applied the conventional approach for examining wind data—Fryberger’s drift equations and the latest Copernicus ERA5 wind reanalysis model—to demonstrate that the Karakum and Kyzylkum deserts had (and continue to have) low-energy environments during 1950–2019. Time-series multidimensional raster analysis and data mining indicated that 93% of surveyed desert areas were subjected to low-energy wind conditions during the last 70 years. The decrease in wind energy was further confirmed using the partitioning around medoids (PAM) unsupervised machine-learning clustering method and Getis-Ord Gi* statistics. Such an environmental setting promotes plant growth and biogenic crust development, and strengthens dune stability across the deserts. Furthermore, the results suggested that the spatial patterns of active dune morphologies (e.g., complex barchanoid ridges and overlaying superimpositions) were closely linked to the drift direction, power, and variability of contemporary winds, whereas stabilized aeolian formations (e.g., distinct formations of complex and compound vegetated linear dunes) indicated debatable disassociations. The relationship between the recognized orientation of the surveyed dune types and the computed resultant drift direction did not change significantly, suggesting that over time, the winds in these areas have most likely varied in strength, but not in direction. The calculated drift powers are not sufficient for the formation of registered mega profiles. Rather, they bolster dunes stability, stressing both deserts as indicative of earlier climatic eras that permitted aeolian sand activity and severe shifts that have initiated their steadiness. This is the first comprehensive study to statistically evaluate the links between the contemporary climate and dune morphologies of the Karakum and Kyzylkum deserts. Our study can serve as a foundation for future studies on climate change, dune mapping, and optically stimulated luminescence (OSL) dating, while offering a broad understanding of the region’s paleo and contemporary environmental systems dynamics.